Rutin attenuates bleomycin-induced acute lung injury via miR-9-5p mediated NF-κB signaling inhibition: network pharmacology analysis and experimental evidence - Alatawi, Fatema S.; Omran, Awatif M. E.; Rashad, Eman; Abdel-Rahman, Omnia N.; Soliman, Ahmed F. (Frontiers in Pharmacology, 2025)
IntroductionAlthough successfully used as a chemotherapeutic agent in various malignant diseases, acute lung injury (ALI) is one of the major limitations of bleomycin (BLM). Seeking reliable natural remedies, this study aimed to explore the potential effect of rutin on BLM-induced ALI.MethodsTargets of rutin and ALI were collected using various databases. Enrichment analyses of common targets were conducted, a protein-protein interaction (PPI) network was constructed, the hub genes were identified, and the upstream miRNA interacting with the top hub gene was later predicted. A BLM-induced ALI rat model was established to verify rutin potential effects, and the selected hub gene expression with its upstream regulatory miRNA and a downstream set of targets were examined to elucidate the action mechanism.ResultsA total of 147 genes have been identified as potential therapeutic targets of rutin to treat BLM-induced ALI. Data from the enrichment and PPI analyses and the prediction of the upstream miRNAs indicated that the most worthwhile pair to study was miR-9a-5p/Nfkb1. In vivo findings showed that rutin administration significantly ameliorated pulmonary vascular permeability, inflammatory cells alveolar infiltration, induction of proinflammatory cytokines in the bronchoalveolar lavage fluid, and lung histology. Mechanistically, rutin downregulated the gene expression level of Nfkb1, Ptgs2, Il18, and Ifng, alongside their protein products, NF-κB p50, COX-2, IL-18, and IFN-γ, accompanied by an upregulation of rno-miR-9a-5p, Il10, and IL-10 expression in lung tissues.ConclusionCombining network pharmacology and an in vivo study revealed that miR-9-5p/Nfkb1 axis could mediate the meliorative effect of rutin against BLM-induced ALI.